Brain function effects of exercise interventions for cognitive decline: a systematic review and meta-analysis - Karamacoska, Diana; Butt, Ali; Leung, Isabella H. K.; Childs, Ryan L.; Metri, Najwa-Joelle; Uruthiran, Vithya; Tan, Tiffany; Sabag, Angelo; Steiner-Lim, Genevieve Z. (Frontiers in Neuroscience, 2023)
Exercise is recognized as a modifiable lifestyle factor that can mitigate cognitive decline and dementia risk. While the benefits of exercise on cognitive ageing have been reported on extensively, neuronal effects in adults experiencing cognitive decline have not been systematically synthesized. The aim of this systematic review was to assess the effects of exercise on cognition and brain function in people with cognitive decline associated with dementia risk. A systematic search was conducted for randomized controlled trials of ≥ 4 weeks exercise (aerobic, resistance, or mind-body) that assessed cognition and brain function using neuroimaging and neurophysiological measures in people with subjective or objective cognitive decline. Study characteristics and brain function effects were narratively synthesized, while domain-specific cognitive performance was subjected to meta-analysis. Study quality was also assessed. 5,204 records were identified and 12 unique trials met the eligibility criteria, representing 646 adults classified with cognitive frailty, mild or vascular cognitive impairment. Most interventions involved 40-minute sessions conducted 3 times/week. Exercise improved global cognition (g = –0.417, 95% CI, –0.694 to –0.140, p = 0.003, I2 = 43.56%), executive function (g = –0.391, 95% CI, –0.651 to –0.131, p = 0.003, I2 = 13.28%), but not processing speed or general short-term memory (both p >0.05). Across fMRI and ERP studies, significant neuronal adaptations were found with exercise cf. control throughout the brain and were linked with improved global cognition, memory, and executive function. Cerebral blood flow was also found to improve with ≥24 weeks of exercise, but was not linked with cognitive changes. The cognitive improvements associated with exercise are likely driven by increased metabolic activity, cerebrovascular mechanisms, and neuroplasticity throughout the brain. Our paper shows the promise in, and need for, high-quality trials integrating cognitive and brain function measures to elucidate the functional relationship between exercise and brain health in populations with a high risk of dementia.